The Efficacy of Joint Border Patrols: Assessing the Impact of the Nigeria-Niger ‘Operation Yaki’ on Cross-Border Crime and Community Relations - Ibiang Okoi (Universitas Negeri Makassar, 2025)
This paper presents a comprehensive assessment of ‘Operation Yaki,’ a joint border patrol initiative between Nigeria and Niger, established to combat transborder crime and insecurity in the volatile Sahel region. Set against a backdrop of chronic insecurity characterized by terrorism, arms smuggling, human trafficking, and banditry, the operation represents a critical case study in bilateral security cooperation in Africa. The research investigates the operational efficacy of the joint patrols in suppressing cross-border criminal activities and, with equal emphasis, analyzes their multifaceted impact on community-state relations and inter-communal dynamics along the borderlands. Employing a qualitative methodology that synthesizes policy analysis, security reports, and secondary ethnographic accounts, the paper argues that while Operation Yaki has achieved measurable tactical successes in disrupting criminal logistics and enhancing real-time intelligence sharing, its overall strategic impact is significantly mediated by deep-seated socio-political and structural factors. These include the historical legacy of the colonial border, complex ethnic and kinship ties that transcend state boundaries, local community perceptions of state security forces, and the persistent socio-economic drivers of crime. Findings suggest that the operation, though a necessary and innovative response, often functions within a paradigm of securitization that can inadvertently marginalize border communities, potentially fueling resentment and undermining long-term security. The paper concludes that the efficacy of joint border patrols cannot be judged solely on crime statistics but must be evaluated within a holistic framework that considers community engagement, human security, and developmental interventions. It recommends a recalibration of Operation Yaki towards a more integrated, community-sensitive model of border governance that leverages trust, addresses root causes of instability, and aligns with broader regional security architectures like the Multinational Joint Task Force (MNJTF) and the G5 Sahel.